Peran orang tua terhadap perkembangan anak - Mahsuni, Intan Sukma (Maliki Interdisciplinary Journal, 2024)
A child's development in preschool has a great impact on their future. Family and parents play an important role in providing guidance, support, and a supportive environment for child development. In this context, this article highlights various aspects of the role of parents in child development, including religious, social, and moral education, good parenting, emotional involvement, and support to reach maximum potential. Positive parental involvement plays a crucial role in shaping children's character, academic achievement, and mental health. With a better understanding of the role of parents, it is hoped that a more supportive environment can be created for the growth and development of children.